Race and crime geographies of injustice - Brown, Elizabeth 1976-; Barganier, George 1976- (University of California Press, 2018)
"Race and Crime examines how and why racialized mass incarceration emerged as a new racial management strategy in the United States and explores its impact on the institutions of criminal justice. Elizabeth Brown and George Barganier historicize the issues of race and crime in society by returning to the history of colonial conquest and the emergence of the idea of race. They show how this idea transitions and transforms throughout history and affects the creation of state power, the emergence of new state institutions, and geographies of racial segregation. Finally, they analyze how punishment, the death penalty, and everyday practices of surveillance practiced in and through the police and courts shape the geographical expression of injustice in the United States today."...Provided by publisher
Includes bibliographical references and index
Keywords: Racism in criminology -- United States; Criminal justice, Administration of -- United States; Imprisonment -- United States; Human geography -- United States; Rassismus; Kriminologie; Strafjustiz; USA